Extensivierungserscheinungen und Wüstungen. Bemerkungen zu zwei Beiträgen zum Wüstungsschema - Fehn, Klaus (ERDKUNDE, 1975)
A modified schema of settlement desertion is presented as a result of further considerations arising from a critique of the two excellent and knowledge-advancing papers by Martin Born (see tab. 2). The core features are the differentiation of settlement desertion from extensivisation phenomena using criteria of land use abandonment and the incipient decay of settlement form; the application of the additional terms absolute and relative for the degree of decay of settlement form; the introduction into the terminology of fossil and recent for more precise identification of permanent settlement desertions; and the incorporation of the desertion of workplaces into a settlement desertion schema which is oriented towards the entire cultural landscape.